Trying to understand preeclampsia. A rocky road - Dekker, Gus (Majalah Obstetri & Ginekologi, 2019)
This narrative is not a review, it is just a personal account of a series of pivotal studies that directly influenced my evolving research interest in the pathogenesis and prevention of preeclampsia since the early 1980s'. Studying in Leiden (The Netherlands) in the early 1970's, my introduction into obstetrics was not very positive. The obstetrical teaching, we received, as 3rd year medical students was boring. The focus was very much on the individual plusses and minuses of types of obstetrical forceps. Preeclampsia was a disease caused by ‘salt excess', strict salt restriction the key concept in prevention of preeclampsia in The Netherlands. One of my lecturers told us that disseminated intravascular coagulation (DIC) was the key causal pathophysiologic mechanism in preeclampsia. At this stage one did not realize that the ‘DIC' observations were all based on autopsy findings in women dying of eclampsia and/or HELLP (although that acronym was only introduced by Weinstein1 in 1982). It was Prof Jack Pritchard2 who – already in these years – made the observation that we ‘never die alone – DIC is always there'. For me the ‘DIC' lectures certainly triggered my interest in the haemostatic system.